2010
DOI: 10.1111/j.1523-1739.2010.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level

Abstract: Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 29 publications
(33 reference statements)
0
76
0
Order By: Relevance
“…Past horizon scanning studies in the environmental science field have identified questions using some combination of: (1) a survey to gather as wide a range of opinions in the field as possible, (2) a workshop, and (3) a review process (Sutherland et al, 2006(Sutherland et al, , 2013Rudd et al, 2011;Parsons et al, 2014;Seddon et al, 2014). We used all three stages of this sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Past horizon scanning studies in the environmental science field have identified questions using some combination of: (1) a survey to gather as wide a range of opinions in the field as possible, (2) a workshop, and (3) a review process (Sutherland et al, 2006(Sutherland et al, , 2013Rudd et al, 2011;Parsons et al, 2014;Seddon et al, 2014). We used all three stages of this sequence.…”
Section: Methodsmentioning
confidence: 99%
“…The methods are broadly similar, but have evolved especially with the objectives of making them more rigorous and more transparent. The completed exercises include an assessment of the 100 questions of greatest importance to the conservation of global biological diversity [31], the top 40 priorities for science to inform conservation and management policy in the United States [32], the top questions of importance to the future of global agriculture [33], UK forestry [34] and Canada [35], identifying the big ecological questions inhibiting effective environmental management in Australia [36], identifying the major conservation policy issues that need to be informed by conservation science [37] and identifying the ecological research needs of business [38]. While the outputs of such exercises are dependent on the people involved, methods have been developed to try to ensure the process is democratic and transparent, so reducing the risk of undue influence of particular individuals.…”
Section: Means Of Identifying Priority Ecological Issues For Policy Mmentioning
confidence: 99%
“…(Rudd and others, 2011) Given the rapid changes in both technology and the drivers that affect ecosystems, the USGS must increase its competency to understand, model, map, and forecast the spatial and temporal dynamics of ecosystem drivers and ecosystem responses to management decisions. Strong collaborations within the agency and with partners will be required to integrate knowledge of changing ecosystem conditions and the consequences of these changes into decisions involving terrestrial, freshwater, and marine systems.…”
Section: Valuing Ecosystem and Economic Services Across Land-use Scenmentioning
confidence: 99%